Chlamydia pneumoniae-induced tumour necrosis factor alpha responses are lower in children with asthma compared with non-asthma. Issue 1 (5th May 2018) - Smith-Norowitz, Tamar Anne; Chotikanatis, Kobkul; Weaver, Diana; Ditkowsky, Jared; Norowitz, Yitzchok Meir; Hammerschlag, Margaret R; Joks, Rauno; Kohlhoff, Stephan
Abstract : Introduction: Chlamydia pneumoniae respiratory tract infection has been implicated in the pathogenesis of reactive airway disease and asthma. Innate cytokine responses that are protective of infection with intracellular pathogens may be impaired in patients with asthma. Tumour necrosis factor alpha (TNF-α) is a cytokine related to functions of monocytes and may inhibit C. pneumoniae infection. We investigated TNF-α responses in C. pneumoniae -infected peripheral blood mononuclear cells (PBMCs) in patients with asthma and non-asthma, and whether ciprofloxacin, azithromycin or doxycycline affects TNF-α responses. Methods: PBMC (1.5×10 6 ) from paediatric patients with asthma (n=19) and non-asthmatic controls (n=6) were infected or mock infected for 1 hour with or without C. pneumoniae AR-39 at a multiplicity of infection=0.1, and cultured+ciprofloxacin, azithromycin or doxycycline (0.1 ug/mL) for 48 hours. TNF-α levels were measured in supernatants by ELISA. Results: When PBMC from patients with asthma were infected with C. pneumoniae, levels of TNF-α were significantly lower than in subjects without asthma (48 hours) (5.5±5.6, 38.4±53.7; p=0.0113). However, baseline responses (no infection with C. pneumoniae ) were similar in asthma and non-asthma (1.0±1.7, 1.1±1.2; p=0.89). When PBMC frompatiens with asthma were infected with C. pneumoniae +ciprofloxacin, azithromycin or doxycycline, TNF-α levels increased (25%–45%); this affect was not observed in PBMC from patients without asthma. Conclusions: We identified differences in the quantity of TNF-α produced by C. pneumoniae- infected PBMC in asthma compared with non-asthma.